BIOMONITORING PENCEMARAN AIR MENGGUNAKAN BEKICOT (Achatina fulica) SEBAGAI BIOINDIKATOR LINGKUNGAN - Fadiya Utami; Sulistia Febriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Water pollution is an environmental problem caused by anthropogenic activities such as domestic, industrial, and agricultural waste. One effective method for monitoring water quality is biomonitoring using bioindicator organisms. The snail (Achatina fulica) has the ability to absorb and accumulate pollutants, particularly heavy metals, through its body surface and digestive system. The accumulation of contaminants in snail tissues reflects the surrounding environmental conditions, making it a useful indirect indicator of water quality. In addition, changes in the behavior and physiological responses of the snail can indicate environmental stress caused by pollution. Therefore, Achatina fulica has the potential to serve as an economical and practical bioindicator in water pollution biomonitoring.